The digital art technique manual for illustrators & artists : the essential guide to creating digital illustration and artworks using Photoshop, Illustrator, and other software - Lardner, Joel; Roberts, Paul (Hauppage, NY Barron's, 2012)
"This books shows you how to use the most common digital art software programs that have been designed specifically for artists and illustrators"--Page 4 of cover.
Part 1. Principles of digital illustration : Choosing software -- Introducing the interface: Photoshop -- Introducing the interface: Illustrator -- All about hardware -- Part 2. Starting points : Art principles -- Sketches and roughs -- Developing a concept -- Using references -- Part 3. Image-making techniques : Starting a new digital project : Document formats ; File types and output sizes ; Scanning a drawing ; Scanning unfamiliar objects ; Refining a scan ; Editing a scan ; Drag and drop -- Using layers : Adding fill color ; Creating transparency ; Blending modes ; Using layer masks -- Color and alterations : Selecting colors ; Identifying and altering colors ; Adding flat color ; Image adjustments ; Invert ; Adjusting colors ; Correcting mistakes ; Scale and transformations ; Cutout techniques ; Cropping and cutting: marquee and lasso ; Selecting elements: magic wand ; Adding color: magic wand ; Quick selection ; Cutting out hair ; Refining edges ; Brush and pencil tool ; Create your ideal brush ; Layering, blending, and overlapping ; Digital montage ; Case study: Using layers creatively -- Vector art : Basic shapes ; The pen tool ; Refining paths ; Line weights and styles ; Fills and gradients ; Introducing the pathfinder tools ; Making a logo with the pathfinder tools ; Case study: Creating vector art ; Importing sketches and references ; Illustrator layers ; Live trace ; Custom brushes ; Making pattern swatches ; Making a patterned image ; Case study: Patterns and details -- Characters and figures : References for character development ; Creating movement ; Figure interaction ; Case study: Enhancing a figure -- Location, landscape, and architecture : Location and landscape ; Understanding lighting ; Depth and perspective ; Architectural detail ; Case study: Creating architectural details ; Textures: photographing materials ; Building an image library ; Case study: Using texture to build an image ; Allowing for imperfections -- Stylistic techniques : Creating texture and grain ; Case study: The artist's hand ; Stylistic techniques: lino and woodcut ; Screen print effects ; Case study: Retro styles ; Filters ; Out-of-register duotone ; Halftones and offsets ; Coloring halftones ; Replicating graffiti stencils ; Creating spatter effects ; Pixel art ; Vector-based urban art ; 3D and digital graffiti ; Case study: Digital graffiti -- New contexts : Making animated gifs ; Saving animations ; Stop-motion movies ; Rotoscoping ; Animating in Photoshop ; Finalizing your animation ; Where to go from here -- Part 4. Professional practice : Presentation and promotion -- Web sites and online presence -- Glossary.
"A Quarto book"--Title page verso.
Includes index.
Keywords: Computer art -- Technique